Evaluating the impact of marine protected areas on fisheries - V, Dr. Krishnapriya; Nayak, Dr. Gangadhar; A, Dr. Rengarajan; Ramakant; Nanda, Simranjeet; Rohini, Kasturi; A, Mohamed Jaffar (International Journal of Aquatic Research and Environmental Studies, 2025)
The number of people is constantly increasing. However, natural resources are either declining or staying relatively stable. Fisheries resources are dwindling, much like all other natural resources, hence it is unrealistic to expect them to meet the demands of an expanding human population. In actuality, many of the world's fisheries have maintained a steady output in recent years. The state of the world's fisheries can be attributed to countless factors. Among them, two significant factors that impede the expansion of fisheries resources are environmental degradation and inadequate fisheries management. Many fisheries around the world have declined or even collapsed as a result of environmental contamination and ineffective resource management. Stocking fish in their early life stages is one method of fishery management that can help prevent extinction and encourage widespread production. This technique is used to ensure that coastal and marine regions continue to produce. Only after World War II did people realise how important it was for India's fishing industry to grow. Because of this, marine fisheries have been overfished in several Indian coastal regions over the years. The current study offers a thorough summary of the socioeconomic characteristics, living and working conditions, technological adaptation, employment and income trends of the fishing community, and the effects of marine protected area fisheries.
Keywords: Fishing, Marine fisheries, Socio-economic profiles